THE RELATIONSHIP BETWEEN STUDENTS’ GRAMMAR MASTERY AND WRITING ABILITY ON THE TENTH GRADE STUDENTS OF SMK WIJAYA KUSUMA SURAKARTA - Oktavia Permata Sari; Luqman Al Hakim (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2021)
The present study entitled the relationship between students’ grammar mastery and writing ability on the tenth grade students of SMK Wijaya Kusuma Surakarta. The purpose of this study was to investigate whether there is significant relationship between students’ grammar mastery and writing ability. Quantitative method with correlation design was used to collect the data. Conducted at SMK Wijaya Kusuma Surakarta in the second semester of 2020/2021 academic year, 28 students of the tenth grade were taken as the sample of this study. Random sampling technique is used in this study. The instruments to obtain the data were grammar mastery test and writing test of writing ability. A try out of grammar test was held to know the validity and 12 numbers of items is valid. To analyze the data, Pearson Product Moment formula was used in manual and computer calculations. Based on the data collected, the mean score of grammar test is 8.36 and the mean score of writing test is 75.79. The result of the analysis shows that the coefficient relationship (rxy ) 0.748. Based on the result of this study, it can be concluded that the grammar mastery had positive relationship with the writing ability on the tenth grade students of SMK Wijaya Kusuma Surakarta.   Keywords: Grammar, Writing Ability, Correlational Study